Impuls- und Wärmeaustausch zwischen der Atmosphäre und dem eisbedeckten Ozean - Garbrecht, Thomas (Univ. Bremen, 2001)
Turbulence, ice ridge, polynja, drag coefficient. - Polarstern (PS) cruise ARK XII led into the Laptev Sea and into the Kara Sea. Measurements of atmospheric processes within the polar surface layer were performed by a turbulence probe mounted at the bow crane of the ship.The meteorological conditions during the cruise were characterised by moderate winds and low temperature differences between the atmosphere and the underlying surface.Detailed information about the variation of meteorological parameters and of the surface fluxes were achieved as a function of the surface characteristics. The measurements are used to analyse ... : thesis